Influence of abiotic factors on the antimicrobial activity of chitosan - Tavaria, Freni K.; Costa, Eduardo M.; Gens, Eduardo J.; Malcata, Francisco Xavier; Pintado, Manuela E. (Journal of dermatology, 2013)
In an effort to bypass the adverse secondary effects attributed to the traditional therapeutic approaches used to treat skin disorders (such as atopic dermatitis), alternative antimicrobials have recently been suggested. One such antimicrobial is chitosan, owing to the already proved biological properties associated with its use. However, the influence of abiotic factors on such activities warrants evaluation. This research effort assessed the antimicrobial activity of chitosan upon skin microorganisms (Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli) in vitro when subject to a combination of different abiotic factors such as pH, ionic strength, organic acids and free fatty acids. Free fatty acids, ionic strength and pH significantly affected chitosan's capability of reducing the viable numbers of S. aureus. This antimicrobial action was potentiated in the presence of palmitic acid and a lower ionic strength (0.2% NaCl), while a higher ionic strength (0.4% NaCl) favored chitosan's action upon the reduction of viable numbers of S. epidermidis and E. coli. Although further studies are needed, these preliminary results advocate that chitosan can in the future be potentially considered as an antimicrobial of choice when handling symptoms associated with atopic dermatitis.